Development of Novel Bio-mulberry-Reinforced Polyacrylonitrile (PAN) Fibre Organic Brake Friction Composite Materials. (11th July 2022) - Kumar, Naresh; Natrayan, L.; Kasirajan, G.; Kaliappan, S.; Raj Kamal, M. D.; Patil, Pravin P.; Chewaka, Muse Degefe
Abstract : Natural fibre reinforcement is used in important sectors such as medical, aerospace, automobile, and many other fields. Many articles have reported that natural fibre has the potential to replace synthetic fibres. Natural fibre reinforcement has given good results as a brake friction material. It has already been proven that asbestos causes lung cancer and mesothelioma in brakes. Many people died from the effects of asbestos. According to the World Health Organization's trending brake report, this material leads to serious health issues. This work is going on for the replacement of these materials. Mulberry fibre is a unique material, and PAN fibre is combined with mulberry fibre and used as a brake reinforcement material to replace Kevlar fibre. The brake pads were fabricated with the various wt% of mulberry fibres and PAN fibre [3–12%] with an equal ratio and aramid fibre [3–6%] in the hydraulic hind brake moulding machine. The mechanical, chemical, physical, tribological, and thermal properties were evaluated. MF-2 [6 wt%] mulberry-PAN-fibre-based brake pad composites have shown better results for ultimate shear strength and proof stress, tensile strength, compressive strength, and impact energy.